2020
DOI: 10.3390/arts9040113
|View full text |Cite
|
Sign up to set email alerts
|

Inside and Outside the Market for Contemporary Art in Brazil, through the Experience of Artists and Gallerists

Abstract: In this paper, I seek to extend our understanding of global art markets by focusing on the relationships between different art world agents and their perceived responsibilities and roles in a market considered locally ‘incipient’ and emergent on the global scene. For this purpose, I draw on over 50 interviews with art gallerists, independent art spaces and visual artists represented by them, living in São Paulo and Rio de Janeiro, the two largest clusters of the contemporary art market in Brazil, at a time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although past and present political leaders have emphasized the importance of artists serving and learning from the people (Xinhua, 2014), ironically, when it comes to contemporary art, it is the market insiders and not the state who articulate the social mission of bringing art to the people. This article then has demonstrated that commercial organizations and practices can be involved in the democratization of art, which has received little attention in the literature so far (Brandellero, 2020). This research encourages scholars to examine the role of commercial practices and organizations, such as auction houses and (affordable) art fairs, in increasing public access to contemporary art.…”
Section: Discussionmentioning
confidence: 99%
“…Although past and present political leaders have emphasized the importance of artists serving and learning from the people (Xinhua, 2014), ironically, when it comes to contemporary art, it is the market insiders and not the state who articulate the social mission of bringing art to the people. This article then has demonstrated that commercial organizations and practices can be involved in the democratization of art, which has received little attention in the literature so far (Brandellero, 2020). This research encourages scholars to examine the role of commercial practices and organizations, such as auction houses and (affordable) art fairs, in increasing public access to contemporary art.…”
Section: Discussionmentioning
confidence: 99%